- The 2010 eruption of Eyjafjallajökull volcano, Iceland: Contributions from chemical and Sr-isotopic microanalytical data on tephra. - CIONI, RAFFAELLO; PISTOLESI, MARCO (Geoitalia, 2011)
Abstract su vulcano Islandese per presentazione a FIST 2011